A Kiss for Cade - Copeland, Lori (Eugene, Or. : Harvest House Publishers, 2009)
Forced to decide the fate of his late sister's children, bounty hunter Cade Kolby returns to his hometown and to Zoe Bradshaw but as the attraction between them flares up again, Zoe is determined not to let Cade get close to her heart.
Previous title: The courtship of Cade Kolby.
Keywords: Foster home care -- Fiction; Fiction; Love stories